PREVALENCE, RISK FACTORS AND CLINICAL PRESENTATIONS OF BACTERIAL VAGINOSIS AMONG GROUP OF PREGNANT WOMEN IN LABOR WORD AT MATERNITY TEACHING HOSPITAL IN SULAIMANI CITY - Faris, Gona Othman; Nasir, Sallama Kamel (Journal of Sulaimani Medical College, 2018)
Background Bacterial vaginosis is a major cause of vaginitis during pregnancy and it results in complications like preterm labor and low birth weight. This may be as a result from excessive growth of anaerobic bacteria in the vagina where it either replaces or reduces normal vaginal flora. Objectives To detect prevalence, risk factors and clinical presentation of bacterial vaginosis among pregnant women in Sulaimani Maternity Teaching Hospital Patients and Methods A cross sectional, quantitative-non experimental descriptive design. Sampling technique used was non-probability convenient sampling. The data collection was carried out from 16th December 2016 to 16th April 2017. One hundred women were selected from labor ward and a high vaginal swab was used to obtain discharge from the vagina, then transfer it immediately to Pharma Gen laboratory. Bacterial vaginosis were confirmed by Nugent criteria. Results Prevalence of Bacterial vaginosis was 25%, it was more in the age group of more than 35 years. Most of them were secondary school graduates, housewives, barely sufficient in their economic status, living in urban and were female with 2-4 gravidity. No relation was found between abortion, and early neonatal death with bacterial vaginosis. Excessive vaginal discharge, pruritus, dysuria, white discharge, and fishy odor are common symptoms. Steroids, antibiotics and diabetes mellitus found to be risk factors. Conclusion One quarter of studied women were affected by bacterial vaginosis, common among multigravida and older age. Clinical feature of purities, excessive vaginal discharge, and fishy odor are highly characteristics of this infection. Diabetic women, prolong use of antibiotic or steroid found to be risk factors.
Keywords: Clinical features; Risk factors; Bacterial Vaginosis; Pregnancy